1998
DOI: 10.1007/s001130050227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of internal fixation of symphyseal disruptions under multidirectional dynamic conditions: an experimental analysis simulating gait conditions

Abstract: For the stabilization of the ruptured pubic symphysis, rigid forms of fixation such as plate osteosynthesis and flexible fixations such as wire loops or PDS banding have been recommended. All methods have only been tested by static unidirectional loading until failure of the system. By this experimental arrangement Ecke and Hofmann found comparable results for flexible and rigid methods of internal stabilization of the pubic symphysis. They preferred flexible methods to maintain mobility of the symphysis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The forces applied to the symphysis during this study were based on prior studies of Meissner et al and Walheim et al These authors studied the physiological mobility of the pubic symphysis and the concomitant impacting forces [8,13,31]. Accordingly, when applying physiological forces to the isolated symphysis with the biomechanically significant posterior pelvic ring previously excluded, the symphysis is not able to bear the entire load and will inevitably rupture, independently from any applied osteosynthesis [13]. Consequently, the authors suggested a maximum of + 75 N and a minimum of −75 N during cyclic loading which was adopted in this study in order to ensure a reasonable biomechanical comparison of the tested osteosynthesis methods [13].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The forces applied to the symphysis during this study were based on prior studies of Meissner et al and Walheim et al These authors studied the physiological mobility of the pubic symphysis and the concomitant impacting forces [8,13,31]. Accordingly, when applying physiological forces to the isolated symphysis with the biomechanically significant posterior pelvic ring previously excluded, the symphysis is not able to bear the entire load and will inevitably rupture, independently from any applied osteosynthesis [13]. Consequently, the authors suggested a maximum of + 75 N and a minimum of −75 N during cyclic loading which was adopted in this study in order to ensure a reasonable biomechanical comparison of the tested osteosynthesis methods [13].…”
Section: Discussionmentioning
confidence: 99%
“…The pelvises were mounted into an all-electric industrial loading machine (Instron ElectroPuls ™ E10000 Linear-Torsion, Norwood, MA, USA) (see Fig. 2) and an 8-step testing protocol based on Meissner et al [13] (see Table 1) was applied. In this study, Meissner et al initially tried to simulate full body weight on an isolated symphysis which, 1 3 however, led to the failure of all implants [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations